Determinants of Poor Quality of Life Among Adults Living with HIV and Enrolled in Highly Active Anti-Retroviral Therapy at Public Health Facilities of Arba Minch Town Administration in Southern Ethiopia - Legesse Tesemma A (Dove Medical Press, 2019)
Abel Legesse Tesemma,1 Meseret Girma Abate,2 Zeleke Hailemariam Abebo,2 Wubshet Estifanos Madebo3 1Bona General Hospital, Hawassa, Sidama, Ethiopia; 2Department of Public Health, College of Medicine and Health Science, Arba Minch University, Arba Minch, Ethiopia; 3Department of Nursing, College of Medicine and Health Science, Arba Minch University, Arba Minch, EthiopiaCorrespondence: Zeleke Hailemariam AbeboDepartment of Public Health, College of Medicine and Health Science, Arba Minch University, P.O. Box 21, Arba Minch, EthiopiaTel +251 912471521Email zelehyle@gmail.comBackground: The human immunodeficiency virus (HIV) continues to be a major global public health problem with more than 35 million people worldwide infected so far. Evidence shows that HIV has been compromising the quality of life of people living with HIV (PLWH) even in this era of highly active anti-retroviral therapy (HAART). There has been little research into the quality of life of PLWH receiving HAART in Ethiopia.Purpose: The aim of this study was to assess the quality of life among PLWH attending anti-retroviral therapy at public health facilities of Arba Minch town, Southern Ethiopia, in 2019.Patients and methods: We conducted a cross-sectional study design on 391 randomly selected PLWH who were attending HAART. We used a systematic random sampling technique to select participants in public health facilities of Arba Minch town from February 16 to April 26, 2019. The interviewers administered a structured questionnaire consisting of the WHOQOL-HIV BREF tool to measure the quality of life. Socio-demographic variables of study participants were collected, together with variables related to their clinical status extracted from their clinical records. Percentage mean scores were calculated and the mean of percentage mean scores was taken as the cutoff to categorize participants into two groups representing poor and good quality of life. Simple binary logistic regression and multivariable logistic regression analyses were used to determine significant variables. All variables with p-value ≤ 0.25 in simple binary logistic regression were considered as eligible variables for multivariable logistic regression. Variables with p-value ≤ 0.05 in multivariable logistic regression were considered as predictor variables.Results: Out of the 391 enrolled adult PLWH, 184 of them (47.1%) had poor of overall quality of life status, as estimated by the WHOQOL-HIV BREF tool. Good quality of life was positively associated with recent CD4 count greater than or equal to 500 cell/mm3 (AOR=1.96, 95% CI; 1.18–3.27), absence of depression (AOR=10.59, 95% CI; 6.16–18.21), normal body mass index (AOR=2.66, 95% CI; 1.18–3.27), social support (AOR= 6.18, 95% CI; 3.56–10.75) and no perceived stigma (AOR=2.75, 95% CI; 1.62–4.67).Conclusion: Nearly half of the adult PLWH receiving HAART at Arba Minch town had poor quality of life. High CD4 count, lack of social support, depression, and perceived stigma were associated with poor quality of life of PLWH. PLWH should be encouraged to be part of structured social support systems, such as associations of people living with HIV and mother support groups, in order to improve their social and psychological health. The health system should give attention to counseling on chronic care adherence and nutritional support to improve the quality of life of PLWH receiving HAART.Keywords: HAART.HIV/AIDS, CD4 count, depression, adherence, QOL, PLWH